The Surveillance of Pre-Marital Sexual Behavior in Malang, Indonesia - Anas R H; Suryanto Suryanto; Rika S Triyoga (Health Notions, 2018)
Adolescents are one of the age groups that need serious attention. Good or bad adolescent will have an impact on the life of the country in the future. About 4.5% of men and 0.8% of women aged 15-19 years have had premarital sexual intercourse. This study aims to determine premarital sexual behavior of adolescents who attend high school in Malang. The study design used an observational design with a cross sectional approach. This research was conducted in 2017 with a population of adolescents of high school students from urban and rural areas in Malang. The sample size was 114 students from 2 schools, which were selected by simple random sampling technique. Data were collected through filling in standardized questionnaires that had been used in the IBBS 2011. The results of the analysis showed that there were differences in premarital sexual behavior between high school students in urban and rural areas. The role of the environment is very significant, especially the supervision of parents who can act as a protective factor at the beginning of adolescent premarital sexual behavior. Keywords: Adolescent, Pre-marital behavior